1992
DOI: 10.1073/pnas.89.7.2922
|View full text |Cite
|
Sign up to set email alerts
|

Both p21ras and pp60v-src are required, but neither alone is sufficient, to activate the Raf-1 kinase.

Abstract: Both p2lras and pp6Ov-src are required, but neither alone is sufficient, to activate the Raf-1 kinase ( ABSTRACTThe rqf genes encode a family of cytoplasmic proteins with intrinsic protein-serine/threonine kinase activity. The c-raf gene is the cellular homolog of v-raf, the transforming gene of murine sarcoma virus 3611. The constitutive kinase activity of the v-Raf protein has been implicated in transformation and mitogenesis. The activity of Raf-l, the protein product of the c-raf gene, is normally suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
2

Year Published

1994
1994
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(87 citation statements)
references
References 36 publications
4
81
2
Order By: Relevance
“…Similarly, the transforming ability of oncogenic ras is dependent on c-Raf-1 (62), and unregulated c-Raf-1 protein kinase activity is itself oncogenic (67). The function of all three protooncogenes is closely interconnected because, although Src and Ras can independently activate c-Raf-1, both are required for full c-Raf-1 activation (43,44,68). The same is true for activation of A-Raf but not B-Raf which can be fully activated by oncogenic Ras alone (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the transforming ability of oncogenic ras is dependent on c-Raf-1 (62), and unregulated c-Raf-1 protein kinase activity is itself oncogenic (67). The function of all three protooncogenes is closely interconnected because, although Src and Ras can independently activate c-Raf-1, both are required for full c-Raf-1 activation (43,44,68). The same is true for activation of A-Raf but not B-Raf which can be fully activated by oncogenic Ras alone (44).…”
Section: Discussionmentioning
confidence: 99%
“…B-Raf lacks the tyrosine residues in c-Raf-1 and A-Raf which are phosphorylated by Src, which may explain its lack of sensitivity to activation by Src (44). However, since the activation of c-Raf-1 autokinase activity by v-src is not inhibited by expression of dominant-negative Ha-ras N17 , v-src may at least partially activate c-Raf-1 via a Ras-independent pathway (68).…”
Section: Discussionmentioning
confidence: 99%
“…Raf-1 kinase activation by Ang II was analyzed essentially as described previously (Ohmichi et al, 1992;Williams et al, 1992). Briefly, neuronal cells after Ang II treatment were lysed for 10 min in the lysis buffer (50 mM Tris, pH 7.4, 150 mM NaCl, 10% glycerol, 0.1% SDS, 0.5% sodium deoxycholate, 1% Triton X-100, 2 mM EDTA, 1 mM phenylmethylsulfonyl fluoride, 10 g/ml aprotinin, and 100 M sodium orthovanadate).…”
Section: Measurement Of Ras Raf-1 and Map Kinase Activitymentioning
confidence: 99%
“…Briefly, neuronal cells after Ang II treatment were lysed for 10 min in the lysis buffer (50 mM Tris, pH 7.4, 150 mM NaCl, 10% glycerol, 0.1% SDS, 0.5% sodium deoxycholate, 1% Triton X-100, 2 mM EDTA, 1 mM phenylmethylsulfonyl fluoride, 10 g/ml aprotinin, and 100 M sodium orthovanadate). The lysates were centrifuged at 10,000 ϫ g for 5 min, and supernatants were used for immunoprecipitation with anti-Raf-1 antibody at 4ЊC for 1 hr (Ohmichi et al, 1992;Williams et al, 1992). Immune precipitates were resuspended in 20 l of reaction buffer (20 mM HEPES, pH 7.4, 1 mM NaCl, and 5 mM MgCl 2 ) containing 10 Ci [␥-…”
Section: Measurement Of Ras Raf-1 and Map Kinase Activitymentioning
confidence: 99%
“…Experiments performed using the Sf9 insect cell system to analyze the activation of Raf-1 have revealed that co-expression of Src, Ras, or PKC with Raf-1 led to its activation (9,10,20,31). To develop a simplified system for the analysis of Raf-1 COOH-terminal modifications, we examined whether treatment of Sf9 cells expressing only RIII-⑀ with H 2 O 2 would lead to a shift in electrophoretic mobility similar to that observed in mammalian cells.…”
Section: Mobility Shift Of a Cooh-terminal Raf-1 Fragment In Mammaliamentioning
confidence: 99%